ORGANIZATION OF COMFORTABLE STUDENT DWELLING UNITS - Popov, Aleksey; Melnikova, Irina (Revista Inclusiones, 2020)
The authors propose promising architectural and space-planning design for dwelling units and particular functional zones based on the analysis of ergonomic features of student youth. It is concluded that in Russia, moving the most functions from remote premises directly to the dwelling unit will require increasing room area by 7-8 meters. The research object is buildings and accommodation complexes for the dwelling of university students. The subject of the study is the creation of comfortable dwelling units appropriate to present-day requirements of living conditions, as well as particular functional zones. The area standards for living rooms of various functions and capacity are determined based on the study of filling the room with necessary furniture, observing comfortable working areas, as well as hygienic requirements. It is proposed to allow designing single occupancy rooms with a living space of 9 m2 .